Prevalence selected risk factors and perception of hypertension in a rural community in the district of Matale. - Dhanapala, S (My University, 1994)
The findings of this survey show that hypertension is a significant health problem in the area. The current screening practices in detecting hypertensive are inadequate and also the treatment and control status of inadequate and also the treatment and control status of hypertension among the hypertensive are inadequate. Other than a disease oriented programme to prevent and control hypertension, it is also important to implement factor oriented programmes, e.g. anti-smoking, alcohol, diet, physical exercise etc. in order to prevent and control non-communicable diseases. This study also highlights the importance of an interventional programme to improve the knowledge and attitude towards the disease of hypertension among the general population